RANCANGAN MARKETPLACE HEWAN TERNAK APPLICATION - Fitria Mitha Firnanda; Diki Kusumah (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2020)
Marketplace of livestock is engaged in the business of selling and purchasing which broadly has the activities of selling and purchasing animals. Usually have several system admins who work and control an application system by handling also the development of businessmen in the application, including making reports and managing master data. In this study business process observations were made from observations of free-range applications which have become a unique marketplace specifically for livestock. The business process that is happening right now, that an application provides a place for various pet shops to pour their sales business activities in accordance with the dimensions of the animals they sell, on the other hand also receives intensive care services for animal development for farmers. It takes a long time for a common marketplace application to get a service maintenance partner, and time brackets along with maintenance service wages that are proportional to the value of feed prices, an increase in the amount of food, and season conditions for a sales activity there is no precise analysis. Based on the needs of this matter, a design of a new market place application design is needed which is equivalent to a market place in general, which only has the ability to sell and purchase. In the analysis phase of modeling using Business Process Modeling Notation (BPMN), while the design stage uses Unified Modeling Language (UML). The design of this application will be a guideline in implementing software in future research.